2013
DOI: 10.1590/s1516-14392013005000029
|View full text |Cite
|
Sign up to set email alerts
|

Calcification in vitro of biomineralizated nanohydroxyapatite/superydrophilic vertically aligned multiwalled carbon nanotube scaffolds

Abstract: Nanocomposites based on superhydrophilic vertically aligned multi-walled carbon nanotubes (VAMWCNT-O 2 ) and nanohydroxyapatite (nHAp) are of great interest in bone regenerative medicine. The biomineralization using simulated body fluid (SBF) has been extensively studied to evaluate the bioactivity of biomaterials. Thus, the combination of nHAp and VAMWCNT-O 2 is attractive and promising. The aim of this study was to evaluate the in vitro calcification of nHAp/VAMWCNT-O 2 nanocomposites before and after the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…) [241], as well as extra components like silver nanoparticles [242], carbon nanotubes [243][244][245][246], graphene and graphene oxide [247,248], or magnetic nanoparticles (Fe 3 O 4 ) [93,94,249]. The presence of these dopants in HAp structure significantly contributes to the biostructure and biochemistry, similar to a natural bone [250].…”
Section: -mentioning
confidence: 99%
“…) [241], as well as extra components like silver nanoparticles [242], carbon nanotubes [243][244][245][246], graphene and graphene oxide [247,248], or magnetic nanoparticles (Fe 3 O 4 ) [93,94,249]. The presence of these dopants in HAp structure significantly contributes to the biostructure and biochemistry, similar to a natural bone [250].…”
Section: -mentioning
confidence: 99%
“…Recently, our group showed that nHAp/VAMWCNT produced on Ti substrates were bioactive and induced extracellular matrix calcification [58,59]. However, the present study represents a step forward from this earlier investigation, because here we transferred all the properties of the material to a bioreabsorbable and tridimensional matrix.…”
Section: Nhap Electrodeposition Onto Pla/vamwcnt-gomentioning
confidence: 83%
“…Bone scaffolds should also have suitable mechanical properties and architecture to play their specific role; several synthetic HA-based composite materials with a variety of nanostructured fillers have been prepared [18,19]; among these, multi-walled carbon nanotubes (MWCNT) have performed very well and have attracted particular attention in tissue engineering due to their excellent mechanical properties [20][21][22][23][24]. In addition, the employment of MWCNT in hydroxyapatite-based composites was recently shown to support the growth of osteoblast cells, thus promoting natural bone biomineralization processes [25]. It has been well demonstrated that the biocompatibility of MWCNT can be increased via appropriate oxidative/carboxylation treatments in order to make them more hydrophilic, shorter and dispersible [26].…”
Section: Introductionmentioning
confidence: 99%